Bone within bone as a calcified chronic extra-dural hematoma mimicking ossified chronic subdural hematomas: a rare case report in pediatric patients - Mohan Karki; Yam Bahadur Roka; Abhinash Jha (Egyptian Journal of Neurosurgery)
Abstract Background Calcified chronic extra-dural hematoma is a rare presentation which often can be observed in traumatic or ventriculoperitoneal shunt cases; it can result in mass effect and raised intracranial pressure. It is common in young adults presumably due to relatively lax adhesion of dura to calvarium. Case Presentation We report a case of 10-year-old female who presented in emergency department with complaints of headache, repeated attacks of seizure, disorientation and sudden loss of consciousness for 2 days. She had a history of fall injury two months ago. On physical examination, she was unconscious (GCS-E3V1M4) with 4 mm dilatation of right pupil. Computed tomography scan of head was done that revealed large extra-axial hypodense mass with thick hyperdense calcified layer between brain parenchyma and hypodense mass in right fronto-temporo-parietal convexity causing mass effect with midline shift: s/o calcified chronic subdural hematoma. Emergency operation-right fronto-temporo-parietal craniotomy was performed. It was chronic extradural hematoma which was evacuated along with removal of calcified innermost layer. Postoperative status went uneventful. She was discharged on 15th day of surgery and doing well on follow-up visit. Conclusion We conclude that surgical evacuation of hematoma along with removal of calcified innermost layer is safe and effective for calcified CEDH.